2021
DOI: 10.1111/ecog.05803
|View full text |Cite
|
Sign up to set email alerts
|

Legacy effects of drought on tree growth responses to hurricanes

Abstract: Natural perturbations, including hurricanes and severe droughts, are becoming more frequent and intense in the tropics, yet our understanding of forest responses to these events is still limited. While the relationships between extreme climatic events and tree mortality are frequently studied, responses of trees that survived such perturbations have been rarely reported. Perturbations and their effects can be quite variable, and trees can respond both positively and negatively to them, depending on their sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 90 publications
(121 reference statements)
3
14
0
Order By: Relevance
“…The majority of the species in our study, however, had lower growth during drought. A recent study at the site using four of the same species found a decline on growth during the 2015 drought at higher elevation sites in the LEF for C. schreberiana , C. borinquensis and S. berteroana —results that were largely consistent with our findings (Umaña & Arellano, 2021). However, drought did not result in lower growth for D. excelsa in their study whereas we found that this keystone species, one of the most important species in Puerto Rican wet forests, also experienced one of the highest declines in growth during the 2015 drought, particularly for larger individuals.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The majority of the species in our study, however, had lower growth during drought. A recent study at the site using four of the same species found a decline on growth during the 2015 drought at higher elevation sites in the LEF for C. schreberiana , C. borinquensis and S. berteroana —results that were largely consistent with our findings (Umaña & Arellano, 2021). However, drought did not result in lower growth for D. excelsa in their study whereas we found that this keystone species, one of the most important species in Puerto Rican wet forests, also experienced one of the highest declines in growth during the 2015 drought, particularly for larger individuals.…”
Section: Discussionsupporting
confidence: 92%
“…Increases in tree mortality and growth declines have been associated with severe drought across several neotropical forests (Bretfeld et al, 2018; Engelbrecht et al, 2006; Leitold et al, 2018; Powers et al, 2020; Umaña & Arellano, 2021; Uriarte et al, 2016), which are expected to be exposed to increasing drought frequency and severity (Kooperman et al, 2018; Neelin et al, 2006). Even relatively short periods of decreased rainfall (≥10 days with no rainfall) during the wet season can increase seedling mortality (Engelbrecht et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…montana, which dominate post-disturbance communities (Uriarte et al, 2009(Uriarte et al, , 2019. Umaña & Arellano (2021) studied six tree species at the same location in Puerto Rico and found that C. schreberiana was the species that had the highest growth reduction during drought, consistent with our findings. In their study, D. excelsa was not affected by severe drought and responded favorably to moderate droughts (Umaña & Arellano, 2021).…”
Section: Trade-off Between Drought Tolerance and Hurricane Resiliencesupporting
confidence: 87%
“…Umaña & Arellano (2021) studied six tree species at the same location in Puerto Rico and found that C. schreberiana was the species that had the highest growth reduction during drought, consistent with our findings. In their study, D. excelsa was not affected by severe drought and responded favorably to moderate droughts (Umaña & Arellano, 2021). Dacryodes excelsa is known to have extensive root grafting (Basnet , 1993) that could allow trees to redistribute water and make them less susceptible to drought.…”
Section: Trade-off Between Drought Tolerance and Hurricane Resiliencesupporting
confidence: 87%
See 1 more Smart Citation